The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0134744
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors on the Relative Age Effect in Alpine Ski Racing

Abstract: The relative age effect (RAE), which refers to an over-representation of selected athletes born early in the selection year, was proven to be present in alpine ski racing in all age categories at both national and international levels. However, the influential factors on, or the causal mechanisms of, the RAE are still unknown. Therefore, the aim of the present study was to examine three possible influential factors on the relative age effect in alpine skiing: physical performance, anthropometric characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 31 publications
4
33
2
Order By: Relevance
“…These relative age advantages have led to the RAE phenomenon, which was initially documented in Canadian ice hockey [ 7 ], and since then, its presence has been proven in many other sports, as well. Two recently published review-articles demonstrated that the RAE in soccer [ 8 ] and alpine ski racing [ 9 ] is present in all age categories at both national and international levels. Based on these findings, strategies in the talent development systems in these sports should be changed in order to contribute to more fairness because talent in a sport does not depend on the birth month [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These relative age advantages have led to the RAE phenomenon, which was initially documented in Canadian ice hockey [ 7 ], and since then, its presence has been proven in many other sports, as well. Two recently published review-articles demonstrated that the RAE in soccer [ 8 ] and alpine ski racing [ 9 ] is present in all age categories at both national and international levels. Based on these findings, strategies in the talent development systems in these sports should be changed in order to contribute to more fairness because talent in a sport does not depend on the birth month [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, strategies in the talent development systems in these sports should be changed in order to contribute to more fairness because talent in a sport does not depend on the birth month [ 6 ]. The existence of a RAE indicates that many relatively younger athletes do not get the chance to reach elite level despite their talents and efforts, they often drop out of sport early and go unnoticed [ 10 13 ]. As a consequence, it can be assumed that there is a severe loss of talent due to the existence of the RAE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAEs have been confirmed in many sports, including soccer [1,2], baseball [3,4], basketball [5,6], handball [7], swimming [8,9], track and field [10,11], sumo wrestling [11], rugby [12], and alpine ski racing [13,14]. The attributes of greater height, mass, aerobic power, muscular strength, endurance, and speed provide performance advantages in most sports, giving relatively older children advantages in sporting ability, psychological confidence, instruction, and playing time [15] In addition to physiological and psychological factors, the competition principle has also been considered as an important factor affecting RAEs.…”
Section: Introductionmentioning
confidence: 99%
“…Within the same age category, there can be a difference of almost a full year between the oldest and youngest children. RAEs have been con rmed in many sports, including soccer [1,2], baseball [3,4], basketball [5,6], handball [7], swimming [8,9], track and eld [10,11], sumo wrestling [11], rugby [12], and alpine ski racing [13,14]. The attributes of greater height, mass, aerobic power, muscular strength, endurance, and speed provide performance advantages in most sports, giving relatively older children advantages in sporting ability, psychological con dence, instruction, and playing time [15].…”
Section: Introductionmentioning
confidence: 99%